Nanoparticulate delivery system for insulin: Design, characterization and in vitro/in vivo bioactivity - Reis, Catarina Pinto (2007)
Insulin-loaded alginate-dextran nanospheres were prepared by nanoemulsion dispersion followed by triggered in situ gelation. Nanospheres were characterized for mean size and distribution by laser diffraction spectroscopy and for shape by transmission electron microscopy. Insulin encapsulation efficiency and in vitro release were determined by Bradford protein assay and bioactivity determined in vitro using a newly developed Western blot immunoassay and in vivo using Wistar diabetic rats. Nanospheres ranged from 267 nm to 2.76 [mu]m in diameter and demonstrated a unimodal size distribution. Insulin encapsulation efficiency was 82.5%. Alginate-dextran particles suppressed insulin release in acidic media and promoted a sustained release at near neutral conditions. Nanoencapsulated insulin was bioactive, demonstrated through both in vivo and in vitro bioassays